If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 2y + 3z = 0 Solving 9x + 2y + 3z = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 9x + 2y + -2y + 3z = 0 + -2y Combine like terms: 2y + -2y = 0 9x + 0 + 3z = 0 + -2y 9x + 3z = 0 + -2y Remove the zero: 9x + 3z = -2y Add '-3z' to each side of the equation. 9x + 3z + -3z = -2y + -3z Combine like terms: 3z + -3z = 0 9x + 0 = -2y + -3z 9x = -2y + -3z Divide each side by '9'. x = -0.2222222222y + -0.3333333333z Simplifying x = -0.2222222222y + -0.3333333333z
| 7x=8.2 | | 16x^2+28x+52=0 | | 16m=7m+72 | | -(2-x)-3(6+8x)-7x= | | 16x^2+28+52=0 | | 3(x+8)-2(x-6)=13 | | f(x)=x^2-4x-10 | | (8x^2-3x)-(6x^2-8x)= | | 5x+2-4x=7-10 | | 130+10x=3.5x | | y-160=-8(x-10) | | 22-m=116 | | 100=6y+y^2 | | x+2x+5x=2x+2x+8 | | 2x+10+x+2x-1=196 | | 7.8x-1.4=22.0 | | 2x+12x=3x-15 | | 3x+4+(1-4x)=1+x-27-2(x-16) | | -6(y+5)=-2y-42 | | 3w-30=9(w-8) | | (2x+8-3)(2x+8-3)= | | 9(x+5)=-9x-9 | | 10=-2v+4(v+6) | | (n+5)(n-3)=(n+1)(n-6) | | -36=-4w+6(w-4) | | 15=-16t^2+44t+5 | | 16=6y+7(y+6) | | X^2-2y^2-8y=0 | | 5(1+x^7)=20 | | 3x+4+(1-4x)=1+x-2(x-16) | | 3x-37.5=-3.41 | | -8v+6(v-5)=-28 |